2007
DOI: 10.7326/0003-4819-147-6-200709180-00007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Triglyceride Levels and Risk for Coronary Heart Disease in Young Men

Abstract: Two triglyceride measurements obtained 5 years apart may assist in assessing CHD risk in young men. A decrease in initially elevated triglyceride levels is associated with a decrease in CHD risk compared with stable high triglyceride levels. However, this risk remains higher than in those with persistently low triglyceride levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
91
1
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 30 publications
8
91
1
5
Order By: Relevance
“…in the IFG group, we found that decreasing levels of triacylglycerol reduced the risk of diabetes. Lifestyle changes are associated with changes in triacylglycerol [38]. Yet, decreasing triacylglycerol independently reduced the risk of diabetes in our study, when adjusted for change in alcohol consumption or weight change (not shown).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…in the IFG group, we found that decreasing levels of triacylglycerol reduced the risk of diabetes. Lifestyle changes are associated with changes in triacylglycerol [38]. Yet, decreasing triacylglycerol independently reduced the risk of diabetes in our study, when adjusted for change in alcohol consumption or weight change (not shown).…”
Section: Discussioncontrasting
confidence: 52%
“…Yet, decreasing triacylglycerol independently reduced the risk of diabetes in our study, when adjusted for change in alcohol consumption or weight change (not shown). Another observational study has shown that decreases in triacylglycerol decreased the risk of coronary heart disease, independently of several lifestyle changes and medication, when compared with stable high triacylglycerol [38]. Based on our results, future studies may look further into the degree to which changes in triacylglycerol determine progression to diabetes, as we were unable to sufficiently adjust for lifestyle changes.…”
Section: Discussionmentioning
confidence: 76%
“…This association persisted both in subjects who were overweight and in those who were not. PA is beneficially associated with blood lipids in different populations, especially HDL cholesterol and TG [27][28][29]. One mechanism by which exercise is responsible for lowered TG and increased HDL cholesterol is the increased use of TG as energy during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome definition for CAD in the MELANY study is angiography-proven stenosis of 50% in at least one coronary artery (1,17,18). Follow-up began at participants' first visit to the screening center and ended at the time of CAD diagnosis, death, retirement from military service, or 8th March 2011, whichever came first.…”
Section: Outcomes and Follow-upmentioning
confidence: 99%